Fear and anxiety of dentistry students during the second wave of the COVID-19 pandemic (Research, Society and Development, 2021)
Oral health care is considered a risky practice for COVID-19, mainly due to the generation of aerosols and proximity to the patient. Because of this, dental practice was changed in the face of the pandemic. Thus, the objective was to investigate the perceptions of dentistry students regarding fear and anxiety in relation to patient management and the risk of infection in the context of the COVID-19 pandemic. This is a cross-sectional study carried out with 167 undergraduate dentistry students from a university center in the interior of Ceará. Data collection was carried out between March and April 2021 by completing an online questionnaire subdivided into: sociodemographic data, assessment of fear and insecurity regarding dental care and assessment of anxiety symptoms, through the Anxiety Inventory of Beck. Data were then analyzed using the Statistical Package for Social Sciences (SPSS) 22.0, considering a 95% confidence level and significance of p